Leakage Current Harmonic Index as A Diagnostic Technique for Tool to Assess the Surface Condition Assessment of Aged Insulator Surface Under Varying Humidity - BENISHEIKH, UMAR ALI; Zulkurnain Abdul-Malek (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Leakage current has been widely utilized as an effective means to monitor the pollution severity of outdoor insulators. The indices of the odd harmonic components of the leakage current have proven to be reliable indicators of insulator performance, particularly in the third to fifth harmonic orders. However, significant challenges exist in using these indices to monitor and classify the leakage current of aged insulators under varying harmonic and pollution conditions. This paper introduces the harmonic index K((3/(5+7) ) which employs third up to seventh odd harmonic component of the leakage current as a diagnostic tool to determine the pollution severity of aged insulators under light, medium and heavy contamination levels. The experiments were conducted using 12 different sets of 11kV insulators with varying degrees of aging. The results indicate that the harmonic index Ki for new and moderately aged insulators decreases with an increase in contamination and is lower than that of heavily aged insulators.